Students' perception on bilingual dictionary of financial accounting terminology - Luh Nyoman Chandra Handayani; I Wayan Dana Ardika; Ida Bagus Artha Adnyana; I Made Rai Jaya Widanta; Gusti Nyoman Ayu Sukerti (English, 2020)
Even though a dictionary is said to be more important to be used while students are reading and writing than speaking, but its existence among learners is undebatable. This need becomes much greater when learners are faced with specific terms in certain sciences, such as the science of Financial Accounting. This study aims to determine the students’ perceptions of the existence of the Bilingual Dictionary of Financial Accounting Terminology, entitled: Kamus Istilah Dwibahasa Akuntansi Keuangan. A questionnaire consisting of 17 questions was distributed to 28 students of a bilingual class in the Accounting Department of a state higher education institution in Bali. The questionnaire was distributed in the form of Google Form, while the dictionary that had been planned given in printed version, finally given in the form of a simple e-Dictionary, due to the Covid-19 pandemic. The results of the questionnaire obtained were then analyzed to determine students’ perceptions of this bilingual dictionary. It is found that students were very happy with the existence of this dictionary. This can be seen from the positive responses given to almost all statements raised, which involved 3 aspects, namely: dictionary design, dictionary content, and mechanical aspects, i.e.: matters related to writing, structure, and spelling. Furthermore, the result also shows that the dictionary is able to give bits of help in the students’ learning processes and to motivate students to be more creative in using vocabulary, especially the financial accounting terminology.